Numerical simulation of nanoparticles coagulation in RF-discharge - Kravchenko, O.Yu.; Yushchyshena, Yu.V. (Вопросы атомной науки и техники, 2016)
This paper presents the simulation results of nanoscale dust particles coagulation in capacitive radio-frequency discharge of low pressure in argon. Simulations carried out under the self-consistent kinetic model that takes into account the stochastic nature of the process of dust particles charging and their coagulation using general dynamic equations for aerosols. We analyze the distribution of dust particles by size and charge at different distances from the electrodes. It is shown that a significant number of dust particles of opposite charges present in sheaths, which improves the process of their coagulation, compared with the central region inter-electrode gap. It is shown that the presence of dust particles increases the concentration of electrons in the discharge, as well as increases the average electric potential drop in sheaths.